Reviews of John G. Butcher, The Closing of the Frontier: A History of the Marine Fisheries of Southeast Asia, c. 1850-2000 - Pokrant, Bob (International Maritime Economic History Association, 2006)
Butcher's book is a welcome addition to the growing literature on the history of fisheries. The book focusses on the "extension of the frontiers of fishing" into existing and new fishing grounds and untapped ecological systems in maritime Southeast Asia between 1850 and 2000, which eventually led to stagnation and decline in fish catches and to the closing of the fishing frontier. The main country focus is the Philippines, Indonesia and Thailand.The issue I wish to take up in this review concerns the conceptual framework used in the study, particularly the place accorded to what Butcher defines as "small-scale" fishers in the extension of the fishing frontier, and the substantive and methodological consequences it has for the study.